PEDESAAN DI INDONESIA PADA ABAD 21 - Destiana Saputri; M Aldi Rahman Indra Jaya; Yusuf Perdana (Universitas Hasanuddin, 2023)
This study aims to find out the extent to which technology has influenced changes in rural areas and the impact caused after the presence of technology in rural areas. The research method uses qualitative methods. The results showed that technology can help agriculture from the level of production, implementation, planting, marketing and analysis of the development of the farm itself. The conclusion of this research is that the development of technology will never stop along with the development of the times where in this case technology coexists with humans. In agriculture, technological advances can be seen from the use of tractors, grass removal machines, and water pumps that support rice field waters. One of the communication methods used is the use of internet services, but the existence of internet media must be used with a positive purpose or a healthy Internet.